The role of social and built environments in predicting self-rated stress: A multilevel analysis in Philadelphia - Yang, Tse-Chuan (2010)
Most studies of the predictors of stress focus on individual characteristics. Linking multiple contextual data sources to an individual-level health survey, we explore the associations of both built and social environment determinants with self-rated stress. At the individual level few social factors were significant predictors, though neighborhood trust and food insecurity have independent effects on stress. At the neighborhood level, the presence of hazardous waste sites and traffic volume were determinants of self-rated stress even after controlling for other individual characteristics. The latter two factors are of relevance to public health policy as they are potentially modifiable.